Longitudinal changes of left ventricular hypoplasia and ventricular disproportion in congenital diaphragmatic hernia neonates - Pugnaloni, Flaminia; Bo, Bartolomeo; Leyens, Judith; Capolupo, Irma; Dotta, Andrea; Bagolan, Pietro; Mueller, Andreas; Patel, Neil; Kipfmüller, Florian (Journal of perinatal medicine, 2025)
Objectives Ventricular disproportion, defined as a ratio of right ventricle (RV) end-diastolic diameter to left ventricle (LV) end-diastolic diameter (RV D /LV D ) ≥ 1.1 is commonly observed in neonates with congenital diaphragmatic hernia (CDH) and it is independently associated with adverse outcome. Longitudinal postnatal data on ventricular disproportion of CDH neonates are poorly studied and we aimed to evaluate changes in RV D /LV D through serial echocardiographic studies at selected timepoints in the neonatal period. Methods This retrospective observational study included CDH neonates admitted to the University Children’s Hospital of Bonn between January 2011 and March 2021. RV D /LV D was measured via apical 4-chamber echocardiographic views at admission, 48h of life, pre-surgical repair, pre-extubation, and on day 5 of ECMO support, if applicable. Patients receiving palliative care, experiencing early death, or lacking follow-up echocardiographic data were excluded. Results Of 248 CDH neonates, 80 were excluded, leaving 168 in the final cohort. At baseline, 41.7% had an RV D /LV D  ≥1.1. Mortality (34.3%) and ECMO rates (62.9%) were significantly higher in these patients compared to those with RV D /LV D <1.1. Ventricular disproportion decreased over time: 41.7% at admission, 23.1% at 48h, 15.7% pre-repair, and 9.1% pre-extubation. For ECMO patients, RV D /LV D  ≥1.1 was found in 62.9% at admission, decreasing over time. Non-survivors had significantly higher RV D /LV D at 48h (p=0.020) and pre-extubation (p=0.001). Conclusions In CDH neonates, ventricular disproportion improves over time, but RV D /LV D ≥1.1 remains strongly associated with mortality, particularly in ECMO patients, where non-survivors exhibit persistently elevated RV D /LV D .